2012
DOI: 10.1158/1078-0432.ccr-11-3114
|View full text |Cite
|
Sign up to set email alerts
|

The Pancreas Cancer Microenvironment

Abstract: Pancreatic ductal adenocarcinoma (PDA) is a common and lethal malignancy resulting in more than 250,000 deaths per year worldwide. Despite extensive efforts, cytotoxic and targeted therapies have provided only limited efficacy for patients with PDA to date. One contributing factor to the failure of systemic therapies may be the abundant tumor stromal content that is the characteristic of PDA. The PDA stroma, aptly termed the tumor microenvironment, occupies the majority of the tumor mass, and consists of a dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
956
1
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,133 publications
(981 citation statements)
references
References 99 publications
9
956
1
15
Order By: Relevance
“…Previous studies 1,2 have shown that PDAC has a growthpromoting effect on pancreatic stellate cells in the surrounding connective tissue, and these cells reciprocate by supporting tumour growth and spread. On page 479, Sousa et al 3 investigate the possibility that pancreatic stellate cells directly provide tumour cells with nutrients, in studies using mice and human pancreatic cells.…”
Section: Jurre J Kamphorst and Eyal Gottliebmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies 1,2 have shown that PDAC has a growthpromoting effect on pancreatic stellate cells in the surrounding connective tissue, and these cells reciprocate by supporting tumour growth and spread. On page 479, Sousa et al 3 investigate the possibility that pancreatic stellate cells directly provide tumour cells with nutrients, in studies using mice and human pancreatic cells.…”
Section: Jurre J Kamphorst and Eyal Gottliebmentioning
confidence: 99%
“…A key feature of PDAC is desmoplasia, in which the tumour becomes enmeshed and surrounded by dense, scar-like tissue 1,4 . As well as the tumour cells, desmoplasia involves other cell types, including pancreatic stellate cells, which are mainly responsible for the condition, and immune cells.…”
Section: Jurre J Kamphorst and Eyal Gottliebmentioning
confidence: 99%
“…5,6 Almost a decade ago, checkpoint blockade targeting the programmed death protein 1/programmed death ligand 1 (PD-1/PD-L1) pathway was described as a promising therapeutic target in PC and has been proven to be successful in a variety of other solid tumor entities. [7][8][9] While the importance of PD-L1 in PC immune evasion was confirmed very recently, only preliminary -rather disappointing -data on the potential efficacy of PD-1/PD-L1 blockade is available in PC yet.…”
Section: Introductionmentioning
confidence: 99%
“…There is virtually no practical limitation to the number of promoter constructs that may be generated for cancer-specific targeting, using straightforward molecular cloning techniques. Along these lines, promoters that target the tumor microenvironment (>70% of the PDA tumor mass) may be designed to overcome barriers to drug delivery to neoplastic cells (61). This capability, unique to promoter-driven DTA therapy, provides a stark contrast with conventional pharmacologic approaches to treat PDA, in which no straightforward strategies exist to overcome drug resistance.…”
Section: Discussionmentioning
confidence: 99%